Polarization of Increasing Residential Settlements on the Development of MSMEs in Medan Tuntungan District - Hardianto; Uswatun Hasanah; Rahmad Sembiring (Equivalent : Journal of Economic, Accounting and Management, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are one of the key pillars supporting regional economic growth while also contributing to the improvement of community living standards. The development of MSMEs is influenced not only by internal business factors but also by population dynamics and the characteristics of residential areas, particularly in urban settings. This study aims to examine how the polarization of increasing residential settlements affects the development of MSMEs in Medan Tuntungan District. The analysis focuses on the relationship between population growth and the number of MSMEs in relation to MSME income, as well as comparing MSME development across areas with different levels of residential density. This research adopts a descriptive quantitative approach and applies multiple linear regression analysis. The data consist of primary data collected through questionnaires and interviews with 100 MSME operators in Medan Tuntungan District, along with secondary data obtained from relevant institutions and various literature sources. The independent variables in this study include population growth and the number of MSMEs, while the dependent variable is MSME income. The results indicate that population growth has a positive and significant effect on MSME income. In addition, the number of MSMEs also shows a positive and significant influence on MSME income. Simultaneously, both independent variables significantly affect MSME income in Medan Tuntungan District. These findings suggest that the expansion of residential settlements can serve as an opportunity for MSME development when supported by appropriate policies and empowerment initiatives.